Salviaolate Protects Rat Brain from Ischemia-Reperfusion Injury through Inhibition of NADPH Oxidase - Lou, Zheng; Ren, Kai-Di; Tan, Bin; Peng, Jing-Jie; Ren, Xian; Yang, Zhong-Bao; Liu, Bin; Yang, Jie; Ma, Qi-Lin; Luo, Xiu-Ju; Peng, Jun (Planta Medica, 2015)
Salviaolate is a group of depside salts isolated from Danshen (a traditional Chinese herbal medicine), with ≥ 85 % of magnesium lithospermate B. This study aims to investigate whether salviaolate is able to protect the rat brain from ischemia/reperfusion injury and the underlying mechanisms. Rats were subjected to 2 h of cerebral ischemia and 24 h of reperfusion to establish an ischemia/reperfusion injury model. The neuroprotective effects of salviaolate at different dosages were evaluated. A dosage (25 mg/kg) was chosen to explore the neuroprotective mechanisms of salviaolate. Neurological function, infarct volume, cellular apoptosis, nicotinamide adenine dinucleotide phosphate-oxidase activity, and H2O2 content were measured. In a nerve cell model of hypoxia/reoxygenation injury, magnesium lithospermate B was applied. Cellular apoptosis, lactate dehydrogenase, nicotinamide adenine dinucleotide phosphate-oxidase activity, and H2O2 content were examined. Ischemia/reperfusion treatment significantly increased the neurological deficit score, infarct volume, and cellular apoptosis accompanied by the elevated nicotinamide adenine dinucleotide phosphate-oxidase activity and H2O2 content in the rat brains. Administration of salviaolate reduced ischemia/reperfusion-induced cerebral injury in a dose-dependent manner concomitant with a decrease in nicotinamide adenine dinucleotide phosphate-oxidase activity and H2O2 production. Magnesium lithospermate B (20 mg/kg) and edaravone (6 mg/kg, the positive control) achieved the same beneficial effects as salviaolate did. In the cell experiments, the injury (indicated by apoptosis ratio and lactate dehydrogenase release), nicotinamide adenine dinucleotide phosphate-oxidase activity and H2O2 content were dramatically increased following hypoxia/reoxygenation, which were attenuated in the presence of magnesium lithospermate B (10−5 M), VAS2870 (nicotinamide adenine dinucleotide phosphate-oxidase inhibitor), or edaravone (10−5 M). The results suggest that salviaolate is able to protect the brain from ischemia/reperfusion oxidative injury, which is related to the inhibition of nicotinamide adenine dinucleotide phosphate-oxidase and a reduction of reactive oxygen species production.
Keywords: Salvia miltiorrhiza; Lamiaceae; salviaolate; magnesium lithospermate B; Danshen; ischemia/reperfusion; NADPH oxidase